Analisis Penerapan Protokol Kesehatan Masyarakat Bangkalan: dari Interpretasi Kulturalis-Religiusitas ke Implementasi “Teks Suci” - Masyhudunnury Masyhudunnury (Journal of Islamic Civilization, 2021)
Over a year the COVID-19 pandemic has hit all corners of the world, including remote areas throughout the archipelago. One of the reasons for the government's inopable efforts in dealing with it is that partial non-compliance has been poured in the form of regional legal products. This paper aims to analyze and explore the real non-compliance of the community even though the local government has done its utmost to make the community understand the purpose and noble purpose of the rule. By using literature studies in analyzing empirical phenomena of behavior among the people of Bangkalan district in response to the policy of 'state' in the face of pandemic covid-19. From this research, it was concluded that the 'state' endeavors in this case the Bangkalan District Government and how to handle it in saving the community from Covid-19 protesters with the representation of the pouring of the community will cult a "holy text", noble values understood in pieces. regional law products, both the Regent Regulation and the Regent's Decree. But the effort as a good will of such authority is hindered by the simplicity of understanding and interpretation of most of society's cult of a "sacred text", noble values understood in pieces